2008
DOI: 10.1002/hed.20852
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of T1 glottic carcinoma since the introduction of endoscopic CO2 laser surgery as treatment option

Abstract: Outcome for T1a patients selected for laser surgery is excellent. In patients with larger lesions treated with radiotherapy, outcome is inferior to patients selected for laser surgery, but also to that reported for (unselected) T1a carcinomas treated with radiotherapy in literature. Strategies to improve treatment results in patients deemed unsuitable for laser surgery should be designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 71 publications
3
47
0
Order By: Relevance
“…Recent reports reveal no significant differences in overall survival and cause-specific survival between RT and TLM in early glottic cancer. 4,17 Because both modalities achieve comparable results in terms of patient survival, the choice of treatment between them is strongly influenced by posttreatment voice and quality of life. 2 In the present study, modal F0 in male patients after TLM is significantly higher than in normal subjects, which is similar to the F0 of patients after RT.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports reveal no significant differences in overall survival and cause-specific survival between RT and TLM in early glottic cancer. 4,17 Because both modalities achieve comparable results in terms of patient survival, the choice of treatment between them is strongly influenced by posttreatment voice and quality of life. 2 In the present study, modal F0 in male patients after TLM is significantly higher than in normal subjects, which is similar to the F0 of patients after RT.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, local control (LC) of patients with early-stage glottic cancer has been found to be similar after radiotherapy, laser resection, or partial laryngectomy (2)(3)(4)(5). Historically, patients with T1a glottic cancer were treated in our department with 66 Gy of radiotherapy to the whole larynx (WL) using two lateral wedgedfields with an average field size of 6x6 cm extending from the lower border of hyoid bone to the lower edge of the cricoid cartilage and in the last 6 years using intensity-modulated radiotherapy (IMRT).…”
Section: Introductionmentioning
confidence: 98%
“…Shapshay et al (12) reported successful results by using endoscopic and external approaches together and including a small part of the thyroid cartilage, which encounters with the anterior commissure, in specimen. In addition to early spread and low rates of local control, poor quality of voice after laser excisions in these tumors limits its advantage of use (14). Taylor et al (15) compared primary treatment approaches of RT and TLM in a group of glottic cancer patients with anterior commissure involvement (T1b), and they found no significant difference between the two groups with regard to voice quality.…”
Section: Clinical and Research Impactsmentioning
confidence: 99%